Does a Picture Paint a Thousand Words? Evidence from a Microcredit Marketing Experiment - Giné, Xavier; Mansuri, Ghazala; Picón, Mario (World Bank, 2013)
Female entrepreneurship is low in many developing economies partly due to constraints on women's time and mobility, often reinforced by social norms. We analyze a marketing experiment designed to encourage female uptake of a new microcredit product. A brochure with two different covers was randomly distributed among male and female borrowing groups. One cover featured 5 businesses run by men while the other had identical businesses run by women. We find that both men and women respond to psychological cues. Men who are not themselves business owners, have lower measured ability and whose wives are less educated respond more negatively to the female brochure, as do women business owners with low autonomy within the household. Women with relatively high levels of autonomy shown the male brochure have a similar negative response, while there is no effect on female business owners with autonomy shown the female brochure. Overall, these results suggest that women's response to psychological cues, such as positive role models, may be mediated by their autonomy and that more disadvantaged women may require more intensive interventions.